2015
DOI: 10.1007/s00374-015-1021-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tropical lowland rainforest conversion into rubber and oil palm plantations on soil microbial communities

Abstract: Focusing on Sumatra, a hotspot of tropical lowland rainforest transformation, we investigated effects of the conversion of rainforests into rubber agroforests (Bjungle rubber^), intensive rubber, and oil palm plantations on the communities of litter and soil microorganisms and identified factors responsible for these changes. Litter basal respiration, microbial biomass, total bacterial phospholipid fatty acids (PLFAs), and fungal PLFAs did not vary significantly with rainforest conversion. In litter of convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
127
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 128 publications
(139 citation statements)
references
References 64 publications
12
127
0
Order By: Relevance
“…In line with the study of Krashevska et al (2015), we found the abundance of nonspecific bacterial biomarker FAs to be highest in oil palm plantations while the abundance of specific bacterial biomarker FAs decreased. Based on metagenomics, Schneider et al (2015) also found certain bacteria taxa to be more abundant in oil palm plantations as compared to rainforest.…”
Section: Effect Of Land-use Change On Food Resources Of Soil Faunasupporting
confidence: 89%
See 3 more Smart Citations
“…In line with the study of Krashevska et al (2015), we found the abundance of nonspecific bacterial biomarker FAs to be highest in oil palm plantations while the abundance of specific bacterial biomarker FAs decreased. Based on metagenomics, Schneider et al (2015) also found certain bacteria taxa to be more abundant in oil palm plantations as compared to rainforest.…”
Section: Effect Of Land-use Change On Food Resources Of Soil Faunasupporting
confidence: 89%
“…Investigating the same study sites, Krashevska et al (2015) found the AMF biomarker NLFA in litter to be lowest in rainforest litter and not to differ significantly between land-use systems in soil, whereas we found the proportion of AMF biomarker NLFAs in soil fauna to be highest in rainforest. Investigating the same study sites, Krashevska et al (2015) found the AMF biomarker NLFA in litter to be lowest in rainforest litter and not to differ significantly between land-use systems in soil, whereas we found the proportion of AMF biomarker NLFAs in soil fauna to be highest in rainforest.…”
Section: Effect Of Land-use Change On Food Resources Of Soil Faunamentioning
confidence: 44%
See 2 more Smart Citations
“…Although oil palm is of economic value to farmers and the local regions in which it is grown, it has received environmental and social criticism, often being held responsible for deforestation (Wicke et al, 2011;Vijay et al, 2016;Gatto et al, 2017), biodiversity loss (Fitzherbert et al, 2008;Koh and Wilcove, 2008;Wilcove and Koh, 2010;Carlson et al, 2012;Krashevska et al, 2015), decreased soil carbon stocks (Guillaume et al, 2015Pransiska et al, 2016), and increased greenhouse gas emissions (Allen et al, 2015;Hassler et al, 2017). Similarly, rubber plantations have environmental impacts such as reducing the soil infiltration capacity, accelerating soil erosion, increasing stream sediment loads (Ziegler et al, 2009;Tarigan et al, 2016b), and decreasing soil carbon stocks (Ziegler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%